Appendicular Endometriosis: A Rare Entity (Journal of Shaheed Suhrawardy Medical College, 2018)
A patient having recurrent right sided lower abdominal pain was admitted as with appendicitis. Laparoscopic appendicectomy was done. On histopatholigical examination it was found to be Endometriosis.J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 83-84